Iron and Chronic Kidney Disease: Still a Challenge - Wojtaszek, Ewa; Glogowski, Tomasz; Malyszko, Jolanta (Frontiers in Medicine, 2020)
Anemia is a clinical feature of chronic kidney disease. Most common causes are iron and erythropoietin deficiency. The last two decades have yielded significant advances in understanding the physiology of iron balance, including iron trafficking and the crosstalk between iron, oxygen and erythropoiesis. This also shed new light on the regulation and disturbance of iron homeostasis in CKD and hold the promise for developing new diagnostic and therapeutic tools to improve management of iron disorders. Hepcidin - ferroportin axis has a central role in regulating body iron balance, coordinating communication between tissues and cells that acquire, store and utilize iron. Recent research has revealed bidirectional relationship between FGF23 (bone secreted hormone) and iron status, anemia and inflammation as well as role of erythroferrone. Despite general interest in iron metabolism in kidney disease, studies on less prevalent mode of renal replacement therapy such as peritoneal dialysis or hemodiafiltrations are scarce, slightly more was published on hemodialysis. However, ERFE concentrations and actions are not well characterized in CKD patients. Studies on ERFE in CKD are limited with slightly conflicting results. There are several novel options on the horizon, however clinical data are limited. One should be aware of potential risks and benefits. of novel sophisticated therapies. An inhibition of hepcidin on the different pathways might be also a viable adjunctive therapeutic option in other clinical situations.